Greening flaring process in oil and gas industries / Yuharajan Baskaran - Yuharajan, Baskaran (2021)
The process of burning excess natural gas in the atmosphere is known as gas flaring in the oil and gas industry. It occurs at the onshore and offshore oil and gas production platforms, as well as the processing plant. As a result, a significant proportion of natural gas is squandered. It would be ideal to recover energy from flared natural gas and use it to generate electricity, particularly in an offshore area when electricity is scarce. As a result, more attention should be paid to the efficient use of flared natural gas in offshore oil and gas installations. The energy recovery system, as one of the promising approaches for generating power from flared natural gas in the Central Processing Platform 1, has gotten a lot of attention (CPP1). Through greenhouse gases and other pollutants, gas flaring is one of the most serious environmental issues. These emissions contribute to climate change by having a high global warming potential. Flared gas and its emissions must be measured, and this has proven to be a difficult task. The reduction and recovery of flare gases is a high priority since it satisfies both environmental and economic efficiency goals. In industry, there are several different forms of FGRS, including gas collection and compression, gas-to-liquid, and power generation. A variety of technical problems have hampered FGRS, including a combination of extremely variable flow rates and composition, poor heating value, and low pressure of waste gases. FGRS has enhanced noise and thermal radiation reduction, operating and maintenance expenses, air pollution and gas emission reduction, and reduced fuel gas and steam usage due to environmental and economic concerns. Therefore, in this study, a simulation model was created using the HYSYS simulation software to anticipate the potential energy in terms of power generated from gas flaring in DCPP using a microturbine. The focus has been on recovering and evaluating potential energy from gas flaring, with the case study taking place at the Central Processing Platform 1, the total amount of gas burned at CPP1 is currently 1.48MMscf/d. With the help of the simulation model, a total of 245kW of power may be created. Based on the amount of energy generated and the money required to set up the system, a complete economic analysis was conducted. It is found that the energy recovery system is extremely desirable, with a potential annual savings of RM217,344 during a 7-year payback time. To make use of the gas flaring, it is recommended that an energy recovery system consisting of a microturbine be placed in the Central Processing Platform 1.